RESILIENCE AS A DETERMINANT OF QUALITY OF LIFE IN POST-DISASTER RELOCATION COMMUNITIES: EVIDENCE FROM THE MOUNT SEMERU ERUPTION - Siswanto Agung Wijaya; Diah Priyantini; Nugroho Ari Wibowo; Vijay Wahyu Handoyo Adi (Indonesian Journal of Community Health Nursing, 2026)
Introduction: The 2021 eruption of Mount Semeru caused severe damage and forced the affected residents to be permanently relocated to residential areas. Although relocation improves physical safety, relocated communities continue to face psychological, social, and economic challenges that may affect their well-being. Resilience is recognized as a key factor supporting adaptation after disasters; however, evidence on its association with quality of life in long-term relocation settings remains limited. This study aims to determine the relationship between resilience and quality of life in adults relocated to residential areas.   Method: Analytic correlational study with a cross-sectional design was conducted in January 2024 in Mount Semeru Relocation area. A total of 111 respondents were recruited using purposive sampling, with eligibility based on age (>18 years), residency duration (≥6 months), disaster exposure, literacy, and willingness to participate. Resilience was measured using the Connor–Davidson Resilience Scale (CD-RISC), while quality of life was assessed using the WHOQOL-BREF. Data were analyzed using descriptive statistics and Spearman’s rho correlation.   Result: Most respondents demonstrated moderate resilience, and more than half reported good quality of life. Statistical analysis revealed a significant positive association between resilience and quality of life (r = 0.337; p < 0.001), indicating that individuals with higher resilience tend to experience better physical, psychological, social, and environmental well-being in the resettlement setting.   Conclusion: Resilience is an important determinant of quality of life among communities permanently relocated after the Mount Semeru eruption. Efforts to strengthen psychosocial support, enhance livelihood recovery, and foster social cohesion are essential to improve long-term adaptation and well-being in post-disaster relocation environments.   Keywords: Mount Semeru Eruption, Quality of Life, Relocation, Resilience